The Effect of Economic and Fundamental Factors on the Australian Property Performance - Ramzi Tarazi; Mohammad Zahid Hasan (Asian Academy of Management Journal of Accounting and Finance, 2019)
This study examines the effect of the trade weighted index (TWI) return on the volatility of Australian Real Estate Investment Trusts (REITs). This study also contributes to the existing literature by measuring the impact of the macroeconomics and fundamental factors on the real estate market for three major states in Australia including New South Wales, Victoria, and Queensland. Using monthly house and unit prices and covering the period from 2009 to 2016, this research uses both fixed and random effect panel data models and the vector autoregressive (VAR) model. The findings of the study suggest that the movement of the TWI has positive and statistically significant impact on Australian REITs suggesting the real estate investors expect risk premium on exchange rate factor. The results also purport that both house and unit prices in Australia are exposed to the fluctuations of the fundamental risk factors. Rental yield, a return component, has a positive relationship with the real estate market in New South Wales and Queensland. The findings of the study provide significant insight to the investors in their portfolio formation since they have the understanding of the priced risk factors.